The Newsvendor Problem with Advertising Revenue - WU, Zhengping (Institutional Knowledge at Singapore Management University, 2011)
We study a modified newsvendor model in which the newsvendor obtains a revenue from sales to end users as well as from an advertiser paying to obtain access to those end users. We study the optimal decisions for both a price-taking and a price-setting newsvendor when the advertiser has private information about its willingness to pay for advertisements. We find that the newsvendor's optimal policy excludes advertisers with low willingness to pay and distorts the price and quantity from its system-efficient level to screen the advertiser. Our analysis reveals the different roles that pricing and production quantity play as screening instruments. We perform a numerical analysis to investigate the value of information and the impact of the model parameters.